2016
DOI: 10.1039/c6md00371k
|View full text |Cite
|
Sign up to set email alerts
|

Improved antiviral activity of a polyamide against high-risk human papillomavirus via N-terminal guanidinium substitution

Abstract: We report the synthesis of two novel pyrrole-imidazole polyamides with N-terminal guanidinium or tetramethylguanidinium groups and evaluate their antiviral activity against three cancer-causing human papillomavirus strains. Introduction of guanidinium improves antiviral activity when compared to an unsubstituted analog, especially in IC90 values. These substitutions change DNA-binding preferences, while binding affinity remains unchanged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…They found that presence of N-terminal guanidinium results in improved antiviral activity. 64 This group also studied the interactions of these antiviral polyamides with DNA. 65 Previously, they had reported a series of large hairpin polyamides (with 10 or more rings) with low IC 50 values against HPV and no detectable toxicity.…”
Section: Polyamides Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that presence of N-terminal guanidinium results in improved antiviral activity. 64 This group also studied the interactions of these antiviral polyamides with DNA. 65 Previously, they had reported a series of large hairpin polyamides (with 10 or more rings) with low IC 50 values against HPV and no detectable toxicity.…”
Section: Polyamides Derivativesmentioning
confidence: 99%
“…57,68,69 Bashkin and collaborators hypothesise that even though HBs will be established in the DNA minor groove, the cumulative effect of many hundreds of rigid, crescent polyamides binding to supercoiled DNA is more important for the antiviral activity observed. 64…”
Section: Polyamides Derivativesmentioning
confidence: 99%
“…One such class of drugs that have been shown to target nucleotide moieties are polyamides. Several polyamides have been developed as inhibitors of gene expression and other biological effectors that bind double-stranded DNA in a sequence-specific manner (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), and other polyamides have also been developed as broad-spectrum antivirals for papillomaviruses and polyomaviruses precisely because they do not show sequence-specific binding properties (19)(20)(21)(22)(23)(24)(25); J. K. Bashkin et al, unpublished data). Others have also since discovered nonspecific polyamide effects (26,27).…”
mentioning
confidence: 99%
“…This targeted approach holds great potential for developing effective and safe treatments for viral diseases, including emerging and drug‐resistant viruses. Antisense oligos, siRNAs, and RNA vaccines have been tested successfully as antiviral reagents, and PIPs have joined this club with molecules tested against polyoma and papilloma viruses 114–116 . Furthermore, treating inherited genetic diseases, certain cancers, and viral diseases using nucleic acid‐based small‐molecule drugs to control transcription factors' activity offers tremendous therapeutic potential and is an exciting frontier for drug design and discovery.…”
Section: Discussionmentioning
confidence: 99%